STUDENTS’ SPEAKING PERFORMANCE USING YOUTUBE IN LEARNING - sri Ariani (Journal of English Education and Literature, 2024)
The study emphasizes the usage of integrating multimedia resources, such as YouTube, into language education curricula. By exposing students to a diverse range of authentic, engaging, and pedagogically sound video content, the learning experience was enriched, allowing for more contextualized language practice and the development of practical communication skills. This research intends to find out how the speaking performance of first-grade students after using YouTube as a learning tool on their speaking performance. A total of 30 students of MTS Negeri 3 Lombok Barat were chosen as participants. The method applied in the research was descriptive qualitative method which employed speaking test and interview to find out the students speaking performance in using YouTube.  Speaking test was conducted to assess the students’ English Speaking performance. It revealed the students excellence in content, pronunciation, and vocabulary. However, the students’ performance in grammar and fluency was categorized as good rather than excellent. The researchers assessed the students' speaking scores and categorized their performance into five levels: poor, fair, average, good, and excellent. The results revealed that 42% of the students reached the excellent level, while both the average and good levels accounted for 25% each. The fair and poor levels each represented 4%. Overall, the average students’ speaking performance after learning using YouTube was deemed good, reflecting the students' cognitive and mental readiness.